What does Permafrost mean to you? Inuvialuit and Gwich’in Knowledge Holders’ Perceptions of a Thawing Relation - Gartler, Susanna; Crate, Susan (Anthropologica)

(untitled) (University of Victoria, 2025)
While climate scholarship has detailed the biophysical impacts of Arctic permafrost thaw, less attention has been paid to how permafrost is perceived and lived with. Drawing on community-based research with Inuvialuit and Gwich’in knowledge holders in the Inuvialuit and Gwich’in Settlement Regions of the Western Canadian Arctic, we argue that permafrost is more than frozen ground: it sustains mobility, subsistence, and cultural continuity; and its degradation threatens these life-giving relations. Analyzing Indigenous land users’ narratives through the lenses of perception studies and infrastructure theory—and foregrounding critical Indigenous scholarship—we propose that permafrost can be understood as critical and alimentary infrastructure in a decolonial sense: an essential system and web of relations vital to societal functioning and a good life on the land. By exploring the meanings attributed to permafrost as a material, and how Indigenous land users engage with the ever-changing landscape and the acceleration of change in the Mackenzie Delta, our study highlights how permafrost thaw impacts perpetuate power imbalances of settler colonialism, as well as how Indigenous perspectives draw attention to permafrost as inseparable from land, kinship, and sustenance. This engagement expands infrastructural analysis through Indigenous epistemologies, producing new understandings of both infrastructure and environment in Arctic contexts.